Design of Database Systems with DRAM-only Heterogeneous Memory Architecture - Qiao, Yifan (Data engineering, 2020)
This thesis advocates a novel DRAM-only strategy to reduce the computing system memory cost for the first time, and investigates its applications to database systems. This thesis envisions a low-cost DRAM module called block-protected DRAM, which reduces bit cost by significantly relaxing the DRAM raw reliability and meanwhile employs long error correction code (ECC) to ensure data integrity at small coding redundancy. Built upon the exactly same DRAM technology, today's byte-accessible DRAM and envisioned block-protected DRAM strike at different trade-offs between memory bit cost and native data access granularity, and naturally form a heterogeneous DRAM-only memory system. The practical feasibility of such heterogeneous memory systems is further strengthened by the new media-agnostic and latency-oblivious CPU-memory interfaces such as IBM's OpenCAPI/OMI and Intel's CXL. This DRAM-only design approach perfectly leverages the existing DRAM manufacturing infrastructure and is not subject to any fundamental technology risk and uncertainty. Hence, before NVM technologies could eventually fulfill their long-awaited promises (i.e., DRAM-grade speed at flash-grade cost), this DRAM-only design framework can fill the gap to empower continuous progress and advances of computing systems. This thesis aims to develop techniques that enable relational and NoSQL databases to take full advantage of the envisioned low-cost heterogeneous DRAM system. As the first step, we studied how one could employ heterogeneous DRAM to implement a low-cost tiered caching solution for relational database, and obtained encouraging results using MySQL as a test vehicle.